Cardiac Radiographic Measurements in Ferrets Using the OsiriX MD Programme - Gutiérrez, Alejandro; Ezquerra, Luis J.; Rodríguez, Pedro L.; Jiménez, Joaquín (Frontiers in Veterinary Science, 2022)
To adapt the vertebral heart scale (VHS) in ferrets and identify new scales and tools that allow us to establish the normal heart size by means of radiography more quickly and effectively. Forty healthy European ferrets were used. The measurements were made on all projections, using OsiriX MD software, to evaluate sex effect and variance within the different heart scales. Cardiac measurements were also correlated to VHS and the cardiac dimension in the same projection. Most of the cardiac measurements were significantly different between males and females. The results for the VHS were: right lateral VHS: 5.52 ± 0.28 v; left lateral: 5.55 ± 0.28 v; and dorsoventral VHS: 6.22 ± 0.34 v for males and RL-VHS: 5.24 ± 0.2 v; LL-VHS: 5.25 ± 0.20 v; and DV-VHS: 5.97 ± 0.35 v for females. Regarding the sternebral heart scale (SHS), the values were: RL-SHS: 5.10 ± 0.20 s and LL-SHS: 5.11 ± 0.20 s for males and RL-SHS: 4.67 ± 0.24 s and LL-SHS: 4.67 ± 0.28 s for females. The new measurements based on determining the cardiac area were also marked by clear sexual dimorphism, as shown for the cardiac area-axis: RL-AREA-AXIS: 3.82 ± 0.45 cm2; LL-AREA-AXIS: 3.87 ± 0.41 cm2; ventrodorsal (VD)-AREA-AXIS: 4.59 ± 0.64 cm2; and DV-AREA-AXIS: 4.80 ± 0.50 cm2 for males and RL-AREA-AXIS: 2.39 ± 0.23 cm2; LL-AREA-AXIS: 2.41 ± 0.26 cm2; VD-AREA-AXIS: 3.08 ± 0.45 cm2; and DV-AREA-AXIS: 3.06 ± 0.47 cm2 for females. The cardiac area open polygon (AREA-POL) values were: RL-AREA-POL: 6.78 ± 0.65 cm2; LL-AREA-POL: 6.88 ± 0.68 cm2; VD-AREA-POL: 7.20 ± 0.91 cm2; and DV-AREA-POL: 7.57 ± 0.88 cm2 for males and RL-AREA-POL: 4.28 ± 0.30 cm2; LL-AREA-POL: 4.35 ± 0.35 cm2; VD-AREA-POL: 4.72 ± 0.65 cm2; and DV-AREA-POL: 4.79 ± 0.66 cm2 for females, with similar differences noted from various radiographic projections. A good correlation was noted between VHS and SHS, and between cardiac area measurements and cardiac dimensions.The VHS adapted to ferrets, the SHS, as well as the cardiac area measurements presented in our study are ideal tools for the assessment of cardiac size in ferrets.